How spatial patterns can lead to less resilient ecosystems - David Pinto-Ramos; Ricardo Martinez-Garcia (Proceedings of the National Academy of Sciences, 2026)
Several theoretical models predict that spatial patterning increases ecosystem resilience. However, these predictions rely on simplifying assumptions, such as assuming isotropic and infinitely large ecosystems, and empirical evidence directly linking spatial patterning to enhanced resilience remains scarce. We introduce a unifying framework, encompassing existing models for vegetation pattern formation in water-stressed ecosystems, that relaxes these assumptions. This framework incorporates finite vegetated areas surrounded by desert and allows varying levels of anisotropic environmental conditions that lead to nonreciprocal plant interactions. Under these more realistic conditions, we identify a desertification mechanism, known as nonlinear convective instability in physics but largely overlooked in ecology. These instabilities form when nonreciprocal interactions destabilize the vegetation-desert interface and can trigger desertification fronts even under stress levels where isotropic models predict stability. Importantly, ecosystems exhibiting periodic vegetation patterns are more susceptible to nonlinear convective instabilities than those with homogeneous vegetation, suggesting that spatial patterning may reduce, rather than enhance, resilience. These findings challenge the prevailing view that self-organized patterning enhances ecosystem resilience and provide a framework for investigating how spatial dynamics shape the stability and resilience of ecological systems under changing environmental conditions.